Aura, thanatoplaces, and the construction of thanatourism emotions - Christou, Prokopis A.; Drotarova, Maria Hadjielia (My University, 2021)
The present study addresses thanatourism emotions by focusing on tourists’ individual perceptions and the role of the thanatourism place (referred to as the thanatoplace). The research draws on fifty in-depth interviews with tourists in close and distant proximity from thanatoplaces. The findings illustrate that thanatourism emotions can be conceptualized at the intersection of ‘physical place’ and ‘mental space’. The physical dimension encompasses the actual thanatoplace. Tourists within thanatoplaces generate emotions by connecting instantaneously with the place and its aura. The mental space involves a tourist’s recollection of thanatourism places and the perception of the thanatourism aura. Perceived thanatourism aura relates to the extent to which a tourist acknowledges the significance and value of a thanatoplace. The interaction of physical place and mental space leads to the generation of four ‘states of being’ in relation to thanatourism: the ‘enlightened’, the ‘passing-by’, the ‘reminiscing’, and the ‘forward-looking’. Contributions to research and practice are provided.
Keywords: Dark tourism; Emotions; Aura; Place; Thanatourism; Mari